To Be Financed or Not : The Role of Patents for Venture Capital Financing - Elisabeth Mueller; Dietmar Harhoff; Carolin Haeussler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This paper investigates how patent applications and grants held by new ventures improve their ability to attract venture capital (VC) financing. We argue that investors are faced with considerable uncertainty and therefore rely on patents as signals when trying to assess the prospects of potential portfolio companies. For a sample of VC-seeking German and British biotechnology companies we have identified all patents filed at the European Patent Office (EPO). Applying hazard rate analysis, we find that in the presence of patent applications, VC financing occurs earlier. Our results also show that VCs pay attention to patent quality, financing those ventures faster which later turn out to have high-quality patents. Patent oppositions increase the likelihood of receiving VC, but ultimate grant decisions do not spur VC financing, presumably because they are anticipated. Our empirical results and interviews with VCs suggest that the process of patenting generates signals which help to overcome the liabilities of newness faced by new ventures.
Keywords: L26; O34; O30; G24; L20; 330; biotechnology; intellectual property rights; patents; R&D and venture capital; Biotechnische Industrie; Patent; Unternehmensgründung; Risikokapital; Finanzierung; Deutschland; Großbritannien